Structuring of oils with high PUFA content: Evaluation of the formulation conditions on the oxidative stability and structural properties of ethylcellulose oleogels. (30th March 2023) - Millao, Sonia; Iturra, Nicole; Contardo, Ingrid; Morales, Eduardo; Quilaqueo, Marcela; Rubilar, Mónica
Highlights: Oleogels low in saturated fatty acids and free of trans fatty acids were obtained. Oleogels maintain a high percentage of polyunsaturated fatty acids. Degree of unsaturation of the oils positively impacted the strength of the gel. The oxidative stability of EC oleogels increases with BHT addition. The oleogels produced can be powerful alternatives to low-saturation fats. Abstract: This study evaluated the formulation of ethylcellulose oleogels as a fat substitute, based on oils with a high content of polyunsaturated fatty acids. Optimal processing conditions for canola, linseed, and chia oil oleogels were determined. The results showed that the oxidative stability was affected to a greater extent in chia oil oleogel, however, the addition of BHT improved the oxidative stability, mainly the peroxide value. Linseed and chia oil oleogels with a high content of polyunsaturated fatty acids (64.28 and 73.02 g/100 g, respectively) were obtained despite the reduction of these with respect to their oils, and no trans fatty acids were produced. Chia oil oleogels were shown to exhibit similar physical properties to linseed oil oleogels in terms of firmness (463.51 ± 7.42 g and 443.03 ± 7.14 g respectively) and rheological behavior. Such a structure led to a dominant elastic character of the oleogels to mimic the mechanical properties of animal fat.